The mediating role of attitude and environmental awareness in the influence of green advertising and eco-labels on green purchasing behaviors - Nelson Geovany Carrión-Bósquez; Oscar Ortiz-Regalado; Ivan Veas-González; Franklin Gerardo Naranjo-Armijo; Wilson Fernando Guerra-Regalado (Spanish Journal of Marketing-ESIC)
Purpose – This study aims to identify whether green advertising and eco-labels influence the purchasing behaviors of organic products or whether the influence of such behaviors is presented through the mediating effect of the attitude and environmental awareness of millennials. Design/methodology/approach – This study used a quantitative, correlational and cross-sectional design. A total of 430 millennials participated in the study. The questionnaire consisted of 20 questions, distributed across five variables. It was applied to people outside shopping centers in the city of Quito and Guayaquil, Ecuador. The results were subjected to statistical tests to determine the internal consistency of the instrument. The convergent and discriminant validity of the research model was verified through confirmatory factor analysis and structural equation modeling. SPSS 20 and AMOS 24 were used for statistical analyses. Findings – The study identified that attitude and environmental awareness mediate the relationship between green advertising and green purchasing behaviors, as well as the relationship between eco-labels and green purchasing behaviors. Furthermore, it has been proven that green advertising directly influences the green purchasing behaviors of organic products among millennials, whereas eco-labels do not. Originality/value – This study is among the initial investigations to delineate the connection between elements of green marketing and the buying patterns of organic goods among millennials in an emerging economy. The study provides answers to earlier scholarly inquiries that proposed examining the correlation among the constituents of the theorized framework. El papel mediador de la actitud y la conciencia ambiental en la influencia de la publicidad ecológica y las etiquetas ecológicas en los comportamientos de compra verde Objetivo – El presente estudio tuvo como objetivo identificar si la publicidad verde y las ecoetiquetas influyen en los comportamientos de compra de productos orgánicos, o si la influencia dentro de dichos comportamientos se presenta a través del efecto mediador de la actitud y la conciencia ambiental de los millennials. Diseño/metodología/enfoque – La investigación fue cuantitativa, correlacional y con un diseño transversal. Participaron en el estudio un total de 430 millennials. El cuestionario constó de 20 preguntas distribuidas en cinco variables. Fue aplicado en persona fuera de los centros comerciales en las ciudades de Quito y Guayaquil - Ecuador. Los resultados obtenidos fueron sometidos a pruebas estadísticas para determinar la consistencia interna del instrumento. La validez convergente y discriminante del modelo de investigación fue verificada mediante un Análisis Factorial Confirmatorio y Modelos de Ecuaciones Estructurales. Para el desarrollo de los análisis estadísticos, se utilizaron SPSS 20 y AMOS 24. Resultados – El estudio identificó que la actitud y la conciencia ambiental median la relación entre la publicidad verde y los comportamientos de compra, así como en la relación entre las ecoetiquetas y los comportamientos de compra. Además, se demostró que la publicidad verde influye directamente en los comportamientos de compra de productos orgánicos entre los millennials, mientras que las ecoetiquetas no. Originalidad y valor – Este artículo se encuentra entre las investigaciones iniciales para delinear la conexión entre los elementos del marketing verde y los patrones de compra de productos orgánicos entre los millennials en una economía emergente. El estudio proporcionó respuestas a consultas académicas previas que proponían examinar la correlación entre los componentes del marco teórico propuesto. 态度和环境意识在绿色广告和生态标签对绿色购买行为影响中的中介作用 目的 – 本研究旨在确定绿色广告和生态标签是否影响有机产品的购买行为, 或这种行为的影响是否通过千禧一代的态度和环境意识的中介效应表现出来。 设计/方法/途径 – 本研究采用定量、相关性和横截面设计。共有430名千禧一代参与了研究。问卷由20个问题组成, 分布在五个变量上。问卷在厄瓜多尔基多和瓜亚基尔市的购物中心外分发。结果经过统计测试, 以确定问卷的内部一致性。通过验证性因素分析 和结构方程模型 验证了研究模型的收敛效度和区分效度。统计分析使用SPSS 20和AMOS 24软件完成。 研究结果 – 研究表明, 态度和环境意识在绿色广告与绿色购买行为之间以及生态标签与绿色购买行为之间起到中介作用。此外, 已证明绿色广告直接影响千禧一代对有机产品的绿色购买行为, 而生态标签则没有直接影响。 原创性/价值 – 本研究是最初探讨绿色营销元素与千禧一代在新兴经济体中有机产品购买模式之间关系的研究之一。该研究回答了早期学术研究提出的关于理论框架各组成部分相关性的探讨。